Pyogenic Arthritis of the Facet Joint with Concurrent Epidural and Paraspinal Abscess: A Case Report - Rhyu, Kee-Won (Korean Society of Spine Surgery, 2011)
Pyogenic arthritis of lumber spinal facet joints is an extremely rare condition. There are only 40 reported cases worldwide. Most cases were associated with history of paravertebral injection, which was not found in our patient. At the time of hospital admission, he had no abnormal magnetic resonance image findings. Two weeks later, he developed pyogenic facet joint arthritis associated with paravertebral and epidural abscess. This report is the first to describe delayed presentation of pyogenic arthritis associated with paravertebral abscess and epidural infection.